(untitled) (Research, Society and Development, 2022)
Objective: To verify changes in health profile, quality of life and functionality, along with 2 years in individuals with Parkinson’s diseases involved in a present and online exercise program. Methods: This is a longitudinal study with a quantitative data approach which was carried out in the city of Dracena, located in the interior of the state of São Paulo. Functionality and the general health profile were measured using Timed Up and Go test, blood pressure and PDQ-39 and, in addition to analysis of sociodemographic variables, between 2019 and 2020. The exercise intervention was carried out twice a week, one hour per session and consisted of gait activities, motor coordination, muscle strength, balance, and laterality. All analyses were performed using the SPSS program (version 20.0) and statistical significance was established at 5%. Results: In total, data from 9 people were monitored in person in 2019 and remotely in 2020. Changes were observed in hospital admission parameters, mean values of systolic and diastolic blood pressure, quality of life, mobility, assessment of daily life, communication, and body discomfort. Conclusion: The main result observed was the improvement in the biannual evaluations carried out with the participants in the observed period, covering physical, mental, and social improvement. The non-pharmacological approach showed positive results collaborating with the hypothesis that it is possible to delay or minimize the worsening of the disease and the development of future complications with the regular practice of physical exercises, resulting in improved quality of life.